Molecular models of carcinogenesis in colorectal cancer - Żelazowski, Maciej J.; Bednarek, Andrzej K. (Contemporary Oncology/Współczesna Onkologia, 2010)
Classical pathological examination of colorectal tumours is based on clinical and histological markers, such as: lymphatic invasion of cancer cells, tumour size, or histopathological malignancy grading. The most important prognostic factor is still the stage of tumour development during the diagnosis (TNM classification). However, this classification reflects the phenotype, not the biology of the tumour and is not sufficient in modern medicine. Advances in molecular methods have enabled the introduction of tests estimating the expression of genes/proteins responsible for the rate of tumour progression, biological response to chemotherapy, or ability to metastasise. Colorectal cancer is thought to be a heterogenic disease, which can arise by multiple molecular pathways. Nevertheless, it is very important for new models of molecular carcinogenesis to be formulated, because they facilitate the work of finding new markers. There are numerous arguments showing that morphologically or histologically alike tumours often differ in prognosis or response to the same therapy. That is why the search for new molecular prognostic markers is so important.